2016
DOI: 10.1093/cid/ciw185
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbial Transplants Reduce Antibiotic-resistant Genes in Patients With RecurrentClostridium difficileInfection

Abstract: Patients with recurrent C. difficile infection harbor large numbers of microbes with antibiotic resistance genes. Fecal microbial transplantation eradicates pathogenic organisms and eliminates antibiotic-resistance genes suggesting this may be a viable treatment option to eradicate multidrug resistant bacteria from patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
163
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(173 citation statements)
references
References 31 publications
9
163
0
1
Order By: Relevance
“…The rate of partial ARB decolonization was even higher, at 80%. The reported results are in line with recent observations by Millan et al who reported that FMT used to treat recurrent C. difficile infection reduces the load of antibiotic-resistant genes in the gut of patients heavily pretreated with antibiotics [34].…”
Section: Discussionsupporting
confidence: 92%
“…The rate of partial ARB decolonization was even higher, at 80%. The reported results are in line with recent observations by Millan et al who reported that FMT used to treat recurrent C. difficile infection reduces the load of antibiotic-resistant genes in the gut of patients heavily pretreated with antibiotics [34].…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study of the effects of FMT on the resistome, FMT was associated with a reduction in the number of different categories of resistance as well as the number of individual determinants [23]. This contraction in the resistome was associated with an increase in the genus- and species-level diversity of the microbiota overall and a decrease in enterobacteriaceae, reflecting what is likely an increased concentration of antibiotic resistance determinants in this family of organisms.…”
Section: Antibiotic Effects On the Microbiomementioning
confidence: 99%
“…43,44 Case reports and case series have shown that FMT can effectively reduce the overall number of antibiotic resistance genes as well as eradicate colonic colonization by MDRO. 45,46 Some have advocated for a whole genome sequencing approach to screening for antibiotic resistance while others have indicated that the field is changing too rapidly to establish actionable/understandable platforms and that this approach is much more costly. 47,48 One of the most attractive features of FMT for CDI is that it is a non-antibiotic based approach to treatment of an antibiotic-associated illness.…”
Section: Antibiotic Resistance Screening and The Resistomementioning
confidence: 99%